LARVA TREMATODA PADA SIPUT AIR TAWAR DI AREAL PERSAWAHAN DAERAH ISTIMEWA YOGYAKARTA - Soenarwan Hery Poerwanto; Dian Antika Kusuma Dewi; Giyantolin Giyantolin (BERITA BIOLOGI, 2020)
The life cycle of Digenea subclass trematodes  that mostly involves snails as intermediate host in the larval stage in the form of sporocysts, redia and cercariae. This study aims to determine the species of freshwater snails, populations and stages of trematoda larvae that infect freshwater snails in the paddy fields and also the factors that influence the population of trematoda larvae. This research method uses purposive random sampling. Snails were collected from paddy fields in Sleman Regency, Yogyakarta City and Bantul Regency, Special Region of Yogyakarta. Snails and Trematodes larvae were identified based on morphological characters with a microscope. The results showed that the species of freshwater snail as  an inang antara  of Trematode was Lymnaea sp. (96.9%), Pomacea canaliculata (2.6%), and Brotia sp. (0.5%). The total population of trematoda larvae in freshwater snails was 4329 individuals with the largest population in Sleman Regency (2784 individuals). Trematode larval stages found were sporocysts (4.8%), redia (8.3%), Leptocercous type cercariae (35.2%), and Furcocercous type cercariae (51.7%). The most trematode larvae found in  fresh water snail was  Furcocercous type cercariae. Factor affecting trematode larvae population are the species and abundance of freshwater snail.